2002
DOI: 10.4141/s01-024
|View full text |Cite
|
Sign up to set email alerts
|

A modeling approach to quantifying soil macroaggregate dynamics

Abstract: . 2002. A modeling approach to quantifying soil macroaggregate dynamics. Can. J. Soil Sci. 82: [181][182][183][184][185][186][187][188][189][190]. While several researchers have suggested that soil aggregate turnover is a significant control on organic matter dynamics, the quantification of soil aggregate dynamics has yet to be achieved. Quantification of soil aggregate turnover is essential to testing any hypothesis concerning the relationship between aggregate turnover and organic matter dynamics. The goal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 28 publications
2
24
0
8
Order By: Relevance
“…However, little is known about the temporal dynamics of the aggregate distribution in soils (Plante et al 2002;De Gryze et al 2006;Álvaro-Fuentes et al 2007;Olchin et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about the temporal dynamics of the aggregate distribution in soils (Plante et al 2002;De Gryze et al 2006;Álvaro-Fuentes et al 2007;Olchin et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, two sampling dates are not adequate to provide the basis for accurate quantitative estimates of aggregate turnover. For instance, Plante et al (2002) reported that soil macroaggregate mean residence times in different soils ranged from 4 to 95 days, where aggregate dynamics were generally two to three times more rapid in a Gray Luvisol compared to a Black Chernozem. De Gryze et al (2006) estimated turnover times for macroaggregates and microaggregates to be 30 and 88 days, respectively.…”
mentioning
confidence: 99%
“…Formation of soil aggregates is the most widespread microscale process that leads to the physical separation of SOC, typically labelled as occluded SOC. The relation between aggregation and the stability or accumulation of SOC has been repeatedly demonstrated Moni et al 2010;Monreal et al 1997;Plante et al 2002;Skjemstad et al 1993;Virto et al 2008Virto et al , 2010. Formation of aggregates has conventionally been thought to involve the electrostatic flocculation of soil separates into stable domains 2-20 lm in size (Ghezzehei 2011), which are then bound by organic or inorganic cementing agents (Jastrow 1996;Six et al 2004).…”
Section: Physical Separationmentioning
confidence: 99%
“…Both occluded fractions are mainly allocated in microaggregates, although heavy occluded POM is also found in macroaggregates and thus provide additional information on the C stabilised in that aggregate size class (Golchin et al 1998). Due to the natural turnover of aggregates -5-30 days for macroaggregates (De Gryze et al 2006;Plante et al 2002), 88 days for microaggregates (De Gryze et al 2006) -the POM fractions are periodically redistributed between inside and outside parts of aggregates. Accordingly, the C contents in free and occluded POM can be similar.…”
Section: Introductionmentioning
confidence: 99%